Media Literacy Program for Early Chilhood Teacher to Enhance Children Critical Thinking Skills in Sidoarjo - S.S. Alamiyah; A. Zamzamy; R. Rasyidah (Future Science)
Mass media has become an un-integral part of almost every human beings living today. Include for young children. These children are being exposed to the media at a very young age. Some article report that they had the first contact with media as a user at the age of fewer than two. Meanwhile, children at this age have not developed critical thinking skills yet that they could believe and imitate what they have seen on media. Thus, it is important for adults around children to help children in developing their critical thinking skills and facilitates a good and healthy habit of media use both at home and school. School today are commonly integrate the use of media at school to support their learning, as in TK Al Hikmah Suko sung on Sidoarjo, they use a variety of media to deliver materials in their daily learning. The teachers generally have an ability to use media, however not the entire teachers are aware that media not only has a positive impact but also has a negative impact on children. The teachers also had very limited knowledge about literacy media and how to deliver the skills to the students. This community program is held through workshop and simulation. The program is aimed to increase the teacher knowledge and skills about media literacy and how to integrate the media literacy material into their teaching-learning process. The pre-survey revealed that teachers at TK Al Hikmah have the ability to access, to use the media and understand the media. However, they have little confidence to teach media literacy to the students. At the end of the community program, they have knowledge about media literacy include how to deliver the media literacy skill to increase students critical thinking skills.